A beacon in the dark: COVID-19 course in CVID patients from two European countries: Different approaches, similar outcomes - Milito, Cinzia; Firinu, Davide; Bez, Patrick; Villa, Annalisa; Punziano, Alessandra; Lagnese, Gianluca; Costanzo, Giulia; van Leeuwen, Leanne P. M.; Piazza, Beatrice; Deiana, Carla Maria; d’Ippolito, Giancarlo; Del Giacco, Stefano Renato; et al. (Frontiers in Immunology, 2023)
Background CVID patients present an increased risk of prolonged SARS-CoV-2 infection and re-infection and a higher COVID-19-related morbidity and mortality compared to the general population. Since 2021, different therapeutic and prophylactic strategies have been employed in vulnerable groups (vaccination, SARS-CoV-2 monoclonal antibodies and antivirals). The impact of treatments over the last 2 years has not been explored in international studies considering the emergence of viral variants and different management between countries. Methods A multicenter retrospective/prospective real-life study comparing the prevalence and outcomes of SARS-CoV-2 infection between a CVID cohort from four Italian Centers (IT-C) and one cohort from the Netherlands (NL-C), recruiting 773 patients. Results 329 of 773 CVID patients were found positive for SARS-CoV-2 infection between March 1st, 2020 and September 1st 2022. The proportion of CVID patients infected was comparable in both national sub-cohorts. During all waves, chronic lung disease, “complicated” phenotype, chronic immunosuppressive treatment and cardiovascular comorbidities impacted on hospitalization, whereas risk factors for mortality were older age, chronic lung disease, and bacterial superinfections. IT-C patients were significantly more often treated, both with antivirals and mAbs, than NL-C patients. Outpatient treatment, available only in Italy, started from the Delta wave. Despite this, no significant difference was found for COVID-19 severity between the two cohorts. However, pooling together specific SARS-CoV-2 outpatient treatments (mAbs and antivirals), we found a significant effect on the risk of hospitalization starting from Delta wave. Vaccination with ≥ 3 doses shortened RT-PCR positivity, with an additional effect only in patients receiving antivirals. Conclusions The two sub-cohorts had similar COVID-19 outcomes despite different treatment approaches. This points out that specific treatment should now be reserved for selected subgroups of CVID patients, based on pre-existing conditions.